Cerebral Air Embolism After Pigtail Catheter Drainage for Pneumothorax: A Case Report and Review of the Literature - Chen, Yi; Zheng, Chunhui; Zeng, Qinghui; Zhang, Fangbiao; Tu, Shaosong; Wu, Zhijun (Frontiers in Surgery, 2021)
Objective: Cerebral air embolism (CAE) is an extremely rare but serious complication of pigtail catheter drainage. The aim of the case report is to review our experience in the diagnosis and treatment for CAE after pigtail catheter drainage. Case presentation: In our study, we report a case of CAE following pigtail catheter insertion for pneumothorax. A 50-year-old man was diagnosed with a pulmonary mass in the right lower lobe. He underwent a right lower lobectomy. Pneumothorax was present after the removal of the chest tube. Pigtail catheter drainage was used in order to treat the pneumothorax, which resulted in convulsions, limb stiffness and unconsciousness. A brain computed tomography (CT) scan was immediately performed and showed multiple low densities in the right occipital lobe, which was diagnosed as CAE. Assisted breathing, antibiotic treatment and anti-epileptic therapy were used and the patient gradually improved and discharge at 27 days of treatment but the muscle strength of the left limb was weakened. Conclusion: We analyzed and summarized the possible causes of CAE in the literature, and the findings of the case could be enhance the vigilance of clinicians.